A novel high capacity space efficient heat storage system for domestic application - Ramadan Mohamed, Elamin Awad (2018)
Solar energy assisted heat pump (SAHP) and Direct Expansion Solar Assisted Heat Pump (DX-SAHP) systems are among the promising means of reducing the consumption of fossil fuels for heat production in residential building applications. The research in this thesis introduces a novel system that integrates solar energy, THS storage, and DX-SAHP. The objective is to develop an efficient heating system for existing homes in the cold climatic region which is sustainable and acts as an alternative to the conventional high energy loss domestic water and space heating systems. One of the prospective techniques of producing and storing of thermal energy is the application of thermochemical materials. Storage of heat in salt hydrates provides an efficient and compact way of storing energy. Hence, the properties of salt hydrates that determine the storage capacity are being investigated. An experimental test has undertaken to assess the effect of integrating the new design of thermochemical storage materials with a solar-assisted multifunctional heat pump system. This research presents a novel design that involves the integration of DX-SAMHP and a hot water tank with a thermochemical sorption jacket. Investigations have been carried out to determine a suitable temperature range for household heating systems. Expanded Vermiculite (host matrix) and CaCl2 (hygroscopic salt) have been used as composite material in an adsorbent reaction jacket for a domestic water tank. The new design has a total volume of 20 kg of V/CaCl2, which can store the thermal energy with a complete reaction. The results show the high capability of the tested materials to enhance the domestic heating system performance when applied in cold regions. The feasibility of the designed system for residential space and water heating is also demonstrated. The maximum energy density obtained through the discharging process is 565 kJ/kg. It is also revealed that the coupling of thermochemical heat storage and heat pump increases the thermal production capacity by 1.166 kWh during the discharging process.